Ectopic right parietal pleural thymic carcinoma: a rare case and review of the literature - Zhu, Haoshuai; Lei, Yiyan; Zou, Jianyong; Su, Chunhua; Zeng, Bo; Li, Yan; Luo, Honghe (Journal of Thoracic Disease, 2017)
ctopic thymic carcinoma is extremely rare. We present a case of a 73-year-old male patient with ectopic right parietal pleural thymic carcinoma and performed a literature review. Computed tomography (CT) of the chest demonstrated a sharp-edged soft tissue mass with intense enhancement measuring 47 mm × 29 mm with a broader base adjacent to the right axillary chest wall at the level of the 5th rib. There was no hilar or mediastinal lymphadenopathy or evidence of a mediastinal tumor or pleural nodules. A totally extra-pleural tumor resection and partial right lung resection was performed. Histological examination demonstrated infiltrative growth typical of carcinoma cells with a nest-like distribution locally invading the surface of the lung tissue. Immunohistochemical examination confirmed the diagnosis of thymic squamous carcinoma positive for CD5. Mediastinal radical radiotherapy (60 Gy) was performed postoperatively. The patient was followed for 17 months without any evidence of recurrence or metastasis.